KENDALI ROBOT MANUAL 4WD MECANUM WHEEL BERBASIS PID DENGAN MENGGUNAKAN ARM â CORTEX M4. - Wahyuono, Toto Alfian; Widyantara, Helmy; Wibowo, Madha Christian (Journal of Control and Network Systems, 2015)
Abstract: The Current problem to controlling robot is motion of robot that less smooth and the ability to maneuver in any direction relating to how robots can move according to been ordered by the system, even a command position, speed and acceleration of robot having beat on the wheels when the robot is running due to the absence of a system to handle feedback from the round wheel. 4 wheels of robot , mecanum wheel having a surplus in navigation system especially if used to resolve obstacles. a little different with the omni robot wheel, the installation of omni wheel should be symmetrical and facing each other, while on the wheel mounting mecanum exactly like a regular car. To deal with the control of movement from the manual robot, this final project is used PID algorithms control system. The process to finding the value of the constant is the result of analysis about the characteristics of a motor implemented by using arm cortex-m4 of data obtained from rotary encoder.the manual robots can receive commands from a user perfectly, which is command of speed dan Acceleration accurately and run smoother by using constants Kp = 1, Ki = 0.0000989 & Kd = 0.00000897 that is the analysis result of a chart, with the value of characteristics of a motor kp, Ki, & kd have been tried out.